Three-month cardiac outcomes of survivors of COVID-19 presenting to a district general hospital in West Hertfordshire, UK. (14th October 2021) - Pyae, P K; Navarra, A; Webb, R; Newland-Smith, A; Vancheeswaran, R; Sehmi, J; Barlow, A
Abstract: Background: COVID-19 is novel entity associated with significant morbidity and mortality. Most patients recover completely, however, a proportion describe persistent symptoms consistent with cardiopulmonary disturbance. The long-term cardiac and respiratory outcomes of COVID-19 are not known. Purpose: The aim of this study was to undertake a comprehensive cardiopulmonary assessment of survivors of COVID-19 with post recovery symptoms. The cardiac findings are presented here. Methods: Survivors of COVID-19 presenting to a general hospital in West Hertfordshire between 18 March 2020 and 15 May 2020, were reviewed at 3 months using a structured prespecified protocol. Patients with persistent symptoms and those admitted to the intensive care unit (ICU) were invited to attend a clinical assessment comprising an electrocardiogram (ECG), echocardiography, chest x-ray (CXR) and pulmonary function tests. At follow up, patients were categorised according to disease course: 1) monitored via a community based virtual hospital, 2) admitted for supplemental oxygen, 3) requiring non-invasive ventilation and 4) ICU admission. Results: 448 eligible patients were evaluated by telephone. 11 patients admitted to ICU and 147 patients with persistent symptoms were invited for further assessment. At presentation, hospitalised patients were older, had higher levels of obesity and increased rates of hypertension than those managed virtually (p<0.05). Among hospitalised patients, the degree of pulmonary infiltration on CXR was higher, ROX index for intubation lower, eGFR lower, C-reactive protein levels higher and lymphocyte counts lower, compared to those managed virtually (p<0.05). The prevalence of known respiratory conditions was higher among patients admitted to hospital, with a trend towards statistical significance (p=0.051). There were no differences in the prevalence of known cardiac disorders and other co-morbidities amongst both patient groups (table 1). At follow up, CXR appearances were improved and similar among patients monitored virtually, those admitted for supplemental oxygen, those requiring non-invasive ventilation and those treated on ICU. There were no differences in heart rhythm and ECG parameters in the four patient groups. Left ventricular systolic and diastolic dimensions, Simpson's biplane ejection fraction, left atrial volume and left ventricular filling pressures were similar in all four patient groups. There were no differences in right ventricular dimensions, right ventricular fractional area change, tricuspid annular plane systolic excursion and pulmonary artery systolic pressures among patients irrespective of disease severity (table 2). Conclusions: At 3 months, we identified no differences in ECG indices and echocardiographic parameters of left and right ventricular function among survivors of COVID-19, independent of disease course. The findings of this study argue against significant cardiac sequalae following COVID-19 infection. FUNDunding Acknowledgement: Type of funding sources: None.